2020
DOI: 10.1111/jhn.12738
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with loss: food and eating in women with ovarian cancer on parenteral nutrition

Abstract: The lead author affirms that this manuscript is an honest, accurate and transparent account of the study being reported. The lead author affirms that no important aspects of the study have been omitted and that any discrepancies from the study as planned have been explained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Four papers (reporting on two studies), offered patient, caregiver, and healthcare professional perspectives on the following interventions; percutaneous venting gastrostomy/gastrojejunostomy and home parenteral nutrition. 30 33 One other paper looked at patients’ experiences of a self-management intervention; an educational tool to educate patients on malignant bowel obstruction. 25…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four papers (reporting on two studies), offered patient, caregiver, and healthcare professional perspectives on the following interventions; percutaneous venting gastrostomy/gastrojejunostomy and home parenteral nutrition. 30 33 One other paper looked at patients’ experiences of a self-management intervention; an educational tool to educate patients on malignant bowel obstruction. 25…”
Section: Resultsmentioning
confidence: 99%
“… 31 Other negative aspects included patients considering a venting gastrostomy/gastrojejunostomy as a constant presence; some were afraid to eat, for fear of causing a blockage of the tube. 31 , 32 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The decision by patients to try teduglutide may not be straightforward. One study using questionnaires investigated patient QoL whilst on teduglutide and found it improved over the 24 week study period [20]. It was suggested that this improvement was related to a reduction in PN volume but there was no significant difference in QoL between the teduglutide and placebo groups; although this could have related to the short duration of the study or the tool used to measure QoL [20].…”
Section: Introductionmentioning
confidence: 99%